Gambaran Karakteristik Sifilis di Poliklinik Kulit dan Kelamin Sub Divisi Infeksi Menular Seksual RSUP Sanglah Denpasar/FK Unud Periode Januari 2011-Desember 2013 - Adisthanaya, Surya (E-Jurnal Medika Udayana, 2017)
Syphilis is a sexual transmitted disease, which is cause by the bacterium Treponema pallidum, that can transmit by sexual intercourse and can transmitted from mother to fetus (vertical transmission). This study is a descriptive cross-sectional using a total of 35 sample from secondary data of clinic records in dermatology and venereology clinic sexual transmitted disease sub division Sanglah Hospital/Medical Faculty Udayana period January 2011-December 2013. The results of this study is 35 patients with syphilis in which the number of males were 30 (85.7 %) is higher than women by 5 (14.3 %). The highest group are the age group of 25 to 44 years were 21 (60 %), the highest syphilis stage group is the group stage of secondary syphilis were 19 (54.3 %), and the number of new cases were 24 (68.6 %) higher than the old cases were 11 (31.4 %). It can conclude that syphilis cases in Sanglah Hospital have characteristic features vary in each variable. The results of this study can be used as a basis for further research to cases of syphilis. Keyword : Syphilis, Characteristic, Secondary Data